Study Of Drug Interaction in Diabetes Mellitus Therapy at the Inpatient Installation of Al Islam Hospital Bandung - Nabila Nur Azhari; Fetri Lestari; Lanny Mulqie (Bandung Conference Series: Pharmacy, 2023)
The patient's clinical outcome can be influenced by drug related problems, one of which is drug interactions, because the more complex the therapy carried out, it will be in line with the use of a large number of drugs and the tendency for polypharmacy, so the potential for drug interactions is greater. One of the diseases that can potentially experience drug interactions is type 2 diabetes mellitus, because it has the potential to be prescribed more than two kinds of drugs or even prescribed polypharmacy. This studied aimed to determined the percentage of drug prescriptions that potential to cause drug interactions, determined the mechanism, classification of the impact of drug interactions. The study was conducted analytically observational with retrospective data collection in January-March 2023 using prescription data and medical records of type 2 diabetes mellitus patients hospitalized at Al Islam Hospital Bandung, with purposive sampling technique. From a total of 98 prescriptions, there were 71 prescriptions that had the potential for drug interactions. Consisting of the number of drugs 2- 4 as many as 25 recipes with potential drug interactions 29 (17.37%), while for the number of drugs ≥5 as many as 46 recipes with potential drug interactions 138 (82.63%). Based on the mechanism of drug interactions that occurred, it consisted of pharmacodynamics 142 (85.03%) and pharmacokinetics 25 (14.97%), with the frequency of major severity 5 (3%), moderate 152 (91%) and minor 10 (6%). This study used Stockley’s Drug Interaction E-Book, Drug Interaction Checker and Medscape Drug Interaction Checker to analyze drug interactions. Outcome klinis pasien dapat dipengaruhi oleh drug related problem salah satunya interaksi obat, karena semakin kompleks terapi yang dilakukan maka akan sejalan dengan penggunaan jumlah obat yang banyak dan kecenderungan terjadinya polifarmasi, sehingga potensi interaksi obat semakin besar. Salah satu penyakit yang dapat berpotensi mengalami interaksi obat ialah diabetes melitus tipe 2, karena berpotensi diresepkan lebih dari dua macam obat atau bahkan diresepkan polifarmasi. Penelitian ini bertujuan untuk mengetahui persentase peresepan obat yang berpotensi menimbulkan interaksi obat meliputi mekanisme, klasifikasi tingkat keparahanan dan dampak dari interaksi obat. Penelitian dilakukan secara observasional analitik dengan pengambilan data secara retrospektif pada bulan Januari-Maret 2023 menggunakan data resep dan rekam medik pasien diabetes melitus tipe 2 yang dirawat inap di Rumah Sakit Al Islam Bandung, teknik pengambilan sampel secara purposive sampling. Dari total 98 resep, terdapat 71 resep yang berpotensi mengalami interaksi obat. Terdiri dari jumlah obat 2-4 sebanyak 25 resep dengan potensi interaksi obat 29 (17,37%), sedangkan untuk jumlah obat ≥5 sebanyak 46 resep dengan potensi interaksi obat 138 (82,63%). Berdasarkan mekanisme interaksi obat yang terjadi terdiri dari farmakodinamik 142 (85,03%) dan farmakokinetik 25 (14,97%), dengan frekuensi tingkat keparahan mayor 5 (3%), moderate 152 (91%) dan minor 10 (6%). Penelitian ini Menggunakan E-Book Stockley’s Drug Interaction, Drug Interaction Checker serta Medscape Drug Interaction Checker untuk menganalisis interaksi obat.